2021
DOI: 10.1007/s11894-021-00808-3
|View full text |Cite
|
Sign up to set email alerts
|

Review of ERCP Techniques in Roux-en-Y Gastric Bypass Patients: Highlight on the Novel EUS-Directed Transgastric ERCP (EGDE) Technique

Abstract: Purpose of Review Hepatobiliary complications are common in Roux-en-Y gastric bypass (RYGB) patients. Despite development of multiple surgical and endoscopic access techniques over the years, ERCP using standard duodenoscope remains challenging in these patients due to the altered anatomy. Recent Findings Limited success with enteroscope-assisted and laparoscope-assisted ERCP led to the evolution of the novel EUS-directed transgastric ERCP (EDGE) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 76 publications
0
30
0
4
Order By: Relevance
“…Adolescents preserve muscle and lose fat mass following sleeve gastrectomy Ms Bethany Glassar, Mr Ashish Desai, Dr Simon Chapman, Dr Martha Ford-Adams, Mrs Sarah Mancell, Mrs Fiona Bartlett 1 Kings College Hospital, London, United Kingdom Introduction: Bariatric surgery for obesity is considered effective and safe in morbidly obese adolescents when medical management fails. (1) However, there are conflicting reports of effects on body composition after bariatric surgery in adults (2,3,4) and concerns that rapid weight loss adversely affects skeletal muscle mass. This review aimed to assess muscle and fat mass changes following sleeve gastrectomy (SG) in adolescents.…”
Section: O11mentioning
confidence: 99%
See 3 more Smart Citations
“…Adolescents preserve muscle and lose fat mass following sleeve gastrectomy Ms Bethany Glassar, Mr Ashish Desai, Dr Simon Chapman, Dr Martha Ford-Adams, Mrs Sarah Mancell, Mrs Fiona Bartlett 1 Kings College Hospital, London, United Kingdom Introduction: Bariatric surgery for obesity is considered effective and safe in morbidly obese adolescents when medical management fails. (1) However, there are conflicting reports of effects on body composition after bariatric surgery in adults (2,3,4) and concerns that rapid weight loss adversely affects skeletal muscle mass. This review aimed to assess muscle and fat mass changes following sleeve gastrectomy (SG) in adolescents.…”
Section: O11mentioning
confidence: 99%
“…Dr Wiaam Al-Hasani 1 , Dr Tina Mazaheri 1 , Dr Ruvini N.K Ranasinghe 1 , Dr Nalinda Herath 1 , Dr Randolf Altmeyer 2 , Dr Royce P Vincent 1 , Mr Shamsi El-Hasanii 3 , Dr Georgios K Dimitriadis 4,5 Faculty of Cardiovascular Medicine and Sciences -King's College London, London, United Kingdom…”
Section: P26mentioning
confidence: 99%
See 2 more Smart Citations
“…Data reported by Khara et al confirmed a high success rate among 76 patients in both those who performed LA-ERCP and EDGE (both 100%), with no significant difference in adverse events rate (17%vs. 6%, p = 0.94), even if LA-ERCP had a slightly higher percentage of AEs [ 72 ]. However, variants of EDGE technique have been recently proposed.In 2019, Wang et al reported a case series (10 patients) in which LAMS was exchanged with double pigtail plastic stents at the end of the procedure or after a follow up period in order to permit closure of the fistula.…”
Section: Resultsmentioning
confidence: 99%